Revitalization of Javanese culture as a cultural resilience mechanism against radicalism - Emmanuel Satyo Yuwono; Doddy Hendro Wibowo; Wahyuni Kristinawati; Irene Miracle Philian Goszal (Universitas Sarjanawiyata Tamansiswa, 2025)
This research aims to explore how the revitalization of Javanese culture plays a role in building cultural resilience as a strategy for the prevention of radicalism. Employing a qualitative approach, the study involved in-depth interviews with Javanese cultural experts, former individuals exposed to radical ideologies, religious leaders, and security apparatus personnel experienced in handling extremism. The thematic analysis identified three primary themes: (1) Kejawen values as a cognitive-affective framework that forms cultural resilience; (2) the practice of Gotong Royong (cooperation) as a source of communal resilience that strengthens the sense of connection and collective alertness; and (3) traditional Arts and Rituals as Mechanisms of Local Identity Formation, which functions to protect individuals from seeking alternative identities offered by radical ideologies. These findings confirm that the revitalization of Javanese culture is not merely the preservation of tradition, but rather an adaptive mechanism that reinforces the community's resilience in rejecting the penetration of violent ideologies. Thus, cultural resilience becomes an essential foundation for sustainable radicalism prevention efforts based on local wisdom. The implications of this study emphasize the importance of utilizing local cultural values and practices in a reflective manner in the formulation of community-based radicalism prevention programs, particularly through the strengthening of cultural spaces, values education, and sustained social participation.